U.S. Commission on CIA Activities within the United States records - United States. Commission on CIA Activities within the United States
Testimonies, documents, and staff interviews with witnesses regarding the full range of subjects covered by the commission's final report concerning activities of the U.S. Central Intelligence Agency (CIA) within the U.S. Subjects include the infiltration of dissident groups, opening of private mail, testing of behavior-inducing drugs on citizens, and subjecting foreign defectors to physical abuse and prolonged confinement. Also includes files on other subjects studied by the commission but not included in its final report such as assassinations of foreign leaders.
Ad hoc commission, created by President Gerald R. Ford via Executive Order 11828 on 4 January 1975, charged with determining whether the CIA conducted domestic surveillance and other activities.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Central Intelligence Agency; Assassination; Civil rights -- United States; Defectors -- United States; Detention of persons -- United States; Dissenters -- United States; Governmental investigations -- United States; Human experimentation in medicine -- United States; Human rights -- Government policy -- United States; Intelligence service -- United States; Intelligence service -- Government policy -- United States; National security -- United States; Postal service -- United States; Privacy, Right of -- United States; Torture -- United States